2005
DOI: 10.1097/01.bco.0000182852.21179.1f
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic approach for pediatric spinal deformity

Abstract: Purpose of reviewOver the past 15 years, thoracoscopic techniques have been used for the treatment of spinal deformities in the pediatric population. Several advantages have been proposed over an open thoracotomy in the treatment of large-magnitude spinal deformities, for anterior fusion in the skeletally immature, and for instrumentation of thoracic scoliosis. Complications, mainly pulmonary, from anterior thoracic procedures have also been reported. Recently, large case series of patients treated with thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In order for stakeholders to appropriately balance their needs and concerns when opting for surgery, they must understand the costs, benefits, and risk profiles of those options. Reported benefits of anterior thoracoscopic approaches over fusion include less blood loss 17 , 18 , less muscle dissection 31 , less post-operative pain 32 , fewer levels instrumented 33 , and improved self-image and mental health SRS-22 scores compared to standard open thoracotomy approaches 34 . However, those same studies reported drawbacks including increased operative time, a steep learning curve, and increased incidence of pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…In order for stakeholders to appropriately balance their needs and concerns when opting for surgery, they must understand the costs, benefits, and risk profiles of those options. Reported benefits of anterior thoracoscopic approaches over fusion include less blood loss 17 , 18 , less muscle dissection 31 , less post-operative pain 32 , fewer levels instrumented 33 , and improved self-image and mental health SRS-22 scores compared to standard open thoracotomy approaches 34 . However, those same studies reported drawbacks including increased operative time, a steep learning curve, and increased incidence of pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%